The Challenging Situation of Refugees: Secular and Catholic Ethical Responses (Hekima Review, 2006)
The unravelling of political regimes in the wake of the Cold War, the emergence of a truly global market, and the recurrenceof ethnic and political strife have contributed to massive movements of people and flow of refugees. The second half of the twentieth century witnessed a big number of exiled people. At the end of 2003 the number of refugees around the world was estimated at twelve million and the internally displaced people at twenty three million1. This tragedy of forced migration is a serious attackon the essential human rights and makes a pressing appeal to the awareness of the modern world. The national and international community is challenged and called to establish new policies and strategies that may respond in an appropriate way to this problem.